PERAN KELOMPOK TANI DALAM PENERAPAN TEKNOLOGI PERTANIAN (Forum Penelitian Agro Ekonomi, 2024)
This paper describes roles of farmers’ groups in agricultural technology application. A farmers’ group is defined as a group of farmers informally consolidate themselves based on their common goals in farming activities. Initial spirit of establishing a farmers’ group is to strengthen farmers’ bargaining position, especially in terms of collective purchasing of farm inputs and selling their agricultural products efficiently. Indonesia has a long experience in formation of farmers’ groups since Mass Intensification (BIMAS) and Special Intensification (INSUS) were launched in 1970s-1980s. Currently, most of farmers groups in Indonesia are not formed by farmers themselves, but they are mostly formed as a response to the government program that requires farmers to become members of a farmers’ group. Most of government support for farmers, such as distribution of subsidized fertilizer, agricultural extension, subsidized farm credits and other programs are distributed to farmers’ group or farmers’ groups association. Introduction and promotion of a new technology is also delivered through farmers’ groups. Thus, the roles of a farmers’ group are not only as the means of distributing government assistance and extension services, but also as the agent for new technology adoption.